Repelling neoliberal world-making? How the ageing–dementia relation is reassembling the social. Issue 4 (July 2018) - Latimer, Joanna
Growing old 'badly' is stigmatizing, a truism that is enrolled into contemporary agendas for the biomedicalization of ageing. Among the many discourses that emphasize ageing as the root cause of later life illnesses, dementia is currently promoted as an epidemic and such hyperbole serves to legitimate its increasing biomedicalization. The new stigma however is no longer contained to simply having dementia, it is failing to prevent it. Anti-ageing cultures of consumption, alongside a proliferation of cultural depictions of the ageing–dementia relation, seem to be refiguring dementia as a future to be worked on to eliminate it from our everyday life. The article unpacks this complexity for how the ageing–dementia relation is being reassembled in biopolitics in ways that enact it as something that can be transformed and managed. Bringing together Bauman's theories of how cultural communities cope with the otherness of the other with theories of the rationale for the making of monsters – such as the figure of the abject older person with dementia – the article suggests that those older body-persons that personify the ageing–dementia relation, depicted in film and television for example, threaten the modes of ordering underpinning contemporary lives. This is not just because they intimate loss of mind, or because they are disruptive, but because they do not perform what it is to be 'response-able' and postpone frailty through managing self and risk.